A history of English - Hejná, Míša (Language Science Press, 2022)
Where does today's English language come from? This book takes its readers on a journey back in time, from present-day varieties to the Old English of Beowulf and beyond. Written for students with little or no background in linguistics, and reflecting the latest scholarship, it showcases the variation and change present throughout the history of English, and includes numerous exercises and sample texts for every period. The reverse-chronological approach taken by this book sets it apart from all existing textbooks of the last fifty years. Innovative features also include its focus on variation, multilingualism and language contact, its use of texts from outside the literary canon, and its inclusion of case studies from syntax, sociophonetics and historical pragmatics.